Airflow resistance of wheat bedding as influenced by the filling method - J. Łukaszuk; M. Molenda; J. Horabik; B. Szot; M.D. Montross (Research in Agricultural Engineering, 2008)
A study was conducted to estimate the degree of variability of the airflow resistance in wheat caused by the filling method, compaction of the sample, and airflow direction. Two types of grain chambers were used: a cylindrical column 0.95 m high and 0.196 m in diameter, and a cubical box of 0.35 m side. All factors examined were found to influence considerably the airflow resistance. Gravitational axial filling of the grain column from three heights (0.0, 0.95 and 1.8 m) resulted in the pressure drops of 1.0, 1.3, and 1.5 kPa at the airflow velocity of 0.3 m/s. Consolidation of axially filled samples by vibration resulted in a maximum 2.2 times increase in airflow resistance. The tests with cubical sample showed that in axially filled samples the pressure drop in vertical direction was maximum 1.5 times higher than in horizontal directions. In the case of asymmetrically filled samples, the pressure drop at the airflow velocity of 0.3 m/s in vertical direction Z was found to be 1.3 of that in horizontal direction X and 1.95 times higher than with horizontal direction Y, perpendicular to X. Variations in airflow resistance in values comparable to that found in the present project may be expected in practice.